A Continuum-Atomistic Multi-Timescale Algorithm for Micro/Nano Flows (Communications in Computational Physics, 2008)
A multi-timescale algorithm is proposed for simulating time-dependent problems in micro- and nano- fluidics. The total simulation domain is spatially decomposed into two regions. Molecular dynamics is employed in the crucial interfacialregions and continuum hydrodynamics is adopted in the remaining bulk regions. Thecoupling is through “constrained dynamics” in an overlap region. Our time schemeis based on the time scale separation between the continuum macro time step andmolecular micro time step. This allows the molecular dynamics during one macrotime step to be treated as in quasi-steady state. Therefore, molecular simulation is onlyperformed in two shorter time intervals. Through linear extrapolation of macroscopicvelocities and re-initialization of particle configurations, we can significantly reducethe total computational cost. We demonstrate and discuss our time algorithm throughhybrid simulation of channel flow driven by a sinusoidally moving top wall. Converging results are achieved for cases of large separation of time scale with much lesscomputational cost than with the original hybrid simulation without time extrapolation.